Nd doped CaYAl3O7: exploration and laser performance of a novel disordered laser crystal. Issue 28 (2nd July 2020) - Li, Yang; Jia, Zhitai; Nie, Hongkun; Yin, Yanru; Fu, Xiuwei; Mu, Wenxiang; Zhang, Jian; Zhang, Baitao; Li, Shuchen; Tao, Xutang
Abstract : A novel disordered structure crystal has drawn intense interest as a promising ultrafast laser crystal host for its broad absorption and emission bands. Abstract : A novel disordered structure crystal has drawn intense interest as a promising ultrafast laser crystal host for its broad absorption and emission bands. Herein, a novel disordered crystal of Nd 3+ -doped CaYAl3 O7 (CYAM) was successfully grown using the Czochralski method for the first time. The effective segregation coefficient of Nd 3+ ions in CaYAl3 O7 was calculated to be 0.76. To better understand the intrinsic optical properties, the transmission spectra and refractive index of pure CaYAl3 O7 were measured. A systematic investigation of the crystal structure characteristics, fluorescence lifetime, and polarized absorption and emission cross-sections of the Nd:CYAM crystal at RT was reported. The maximal absorption cross-sections are 3.51 and 5.34 × 10 −20 cm 2 for π-polarization and σ-polarization, with a FWHM of 18 nm. The emission cross-sections of π- and σ-polarization are 5.97 and 4.55 × 10 −20 cm 2 with FWHM values of 14 and 14.4 nm, respectively. The results show that the Nd:CYAM crystal has broad, strong absorption and emission cross-sections. In particular, effective continuous-wave laser operation was realized with this crystal in the a -cut sample for the first time. A maximum output power of 714 mW was achieved, corresponding to an optical-to-optical conversion efficiency of 7.14% and a slope efficiency of 8.6%. Collectively, these results show that the Nd:CaYAl3 O7 crystal is a promising disordered laser host.